Reconstruction of Examination of Marriage Dispensation As a Effort to Protect Children - Nugraha, Alfajar (FENOMENA, 2023)
Abstract Marriage dispensation is one of the problems that is still unfinished to be discussed where there is a lot of debate that the marriage dispensation is a legality of underage marriage on the grounds that the provision of marriage dispensation is not based on child protection even some decisions of the Religious Courts have become a material for criticism where the consideration of the judges' decisions is still considered "not properly constructed both in terms of examination procedures and in terms of substantial legal considerations, therefore the Supreme Court as the highest institution within the scope of the Judiciary has issued Supreme Court Regulation Number 5 of 2019 as a regulatory framework for the judges of course to determine the granting of marriage dispensation to the prospective bride and groom whose age is still below the age of marriage with reference to child protection efforts such as in the absence of coercion, psychological maturity, reproductive health and sexuality, as well as economic and educational readiness of the prospective bride and groom which are seen as factors that must be considered so that child protection efforts can be achieved.